Pediatric Lower Limb Lengthening Using the PRECICE Nail: Our Experience With 50 Cases. Issue 1 (January 2021) - Iliadis, Alexios D.; Palloni, Valentina; Wright, Jonathan; Goodier, David; Calder, Peter
Abstract : Background: Limb lengthening using intramedullary externally controlled motorized devices is becoming increasingly popular. There is limited literature regarding their use in the pediatric and adolescent population. This study reviews outcomes on 50 consecutive cases of intramedullary lower limb lengthening surgery in this population. Methods: A retrospective review of all pediatric and adolescent patients treated in our institution by intramedullary lengthening for lower limb length discrepancy using the PRECICE and STRYDE intramedullary lengthening nails between 2013 and 2019. All patients were operated by a single surgeon. Data were prospectively recorded. We report on nail accuracy and reliability, consolidation index, time to full weight-bearing from completion of lengthening, joint range of movement, ASAMI bone and functional scores, presence of problems, obstacles and complications, and patient reported outcome measures (PROMS). Results: Fifty cases (43 femoral and 7 tibial nails) were performed in 42 patients (20 males, 48% and 22 females, 52%). Six patients had bilateral lengthening and 2 patients had sequential lengthening. There were 28 antegrade femoral, 13 retrograde femoral and 5 tibia PRECICE nails, 2 tibial and 2 femoral PRECICE STRYDE nails. Mean age at surgery was 15 years old (12 to 17). Mean preoperative length discrepancy was 49 mm (20 to 90). Mean achieved lengthening was 46.5 mm (20 to 80). Mean percentage lengthening was 12.6% (5% to 25%). Nail accuracy was 96% and reliability 90%. Average distraction rate was 0.92 mm/d for femur and 0.64 mm/d for tibias. Consolidation index was 28 d/cm (18 to 43) and 39 d/cm (20 to 47), respectively. Time from completion of lengthening to independent full weight-bearing as observed in clinic was 45 days (21 to 70) and 34.2 days (23 to 50), respectively. ASAMI bone and functional scores were favorable and PROMS demonstrated high patient satisfaction levels. No significant complications were observed. Conclusions: We have demonstrated excellent clinical results and high patient satisfaction with intramedullary lengthening in a pediatric/adolescent population. We highly recommend thorough preoperative preparation, patient education, and a multidisciplinary approach. Level of Evidence: Level IV. Abstract : Supplemental Digital Content is available in the text.